2014
DOI: 10.1039/c4cc04498c
|View full text |Cite|
|
Sign up to set email alerts
|

Virtual screening and optimization of Type II inhibitors of JAK2 from a natural product library

Abstract: Amentoflavone has been identified as a JAK2 inhibitor by structure-based virtual screening of a natural product library. In silico optimization using the DOLPHIN model yielded analogues with enhanced potency against JAK2 activity and HCV activity in cellulo. Molecular modeling and kinetic experiments suggested that the analogues may function as Type II inhibitors of JAK2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 25 publications
0
26
0
Order By: Relevance
“…[24] So, to predict the possible anticancer activity mechanism, the investigated substances were also molecularly docked to epidermal growth factor receptor kinase (EGFRK) (1m17.pdb). [21][22][23][24][25][26] Gefiti- nib (N-(3-chloro-4-fluoro-phenyl)-7-methoxy-6-(3-morpholin-4-yl-propoxy)quinazolin-4-amine) was used as a reference. [24] It was found that N-(4-fluorophenyl)- Table S2).…”
Section: Docking Studies To Epidermal Growth Factor Receptor Kinasementioning
confidence: 99%
“…[24] So, to predict the possible anticancer activity mechanism, the investigated substances were also molecularly docked to epidermal growth factor receptor kinase (EGFRK) (1m17.pdb). [21][22][23][24][25][26] Gefiti- nib (N-(3-chloro-4-fluoro-phenyl)-7-methoxy-6-(3-morpholin-4-yl-propoxy)quinazolin-4-amine) was used as a reference. [24] It was found that N-(4-fluorophenyl)- Table S2).…”
Section: Docking Studies To Epidermal Growth Factor Receptor Kinasementioning
confidence: 99%
“…The use of in silico methodology has opened new avenues in the field of drug discovery and development, including in the design of novel chemical inhibitors by protein structural analysis 7 8 , drug library screening using quantitative structure-activity relationship (QSAR) methods 9 10 and multi-scale modelling 11 . Computational fluid dynamics (CFD) is a well known in silico approach used throughout the fields of engineering, physics and increasingly biology.…”
mentioning
confidence: 99%
“…Natural products are indispensable candidates in current drug discovery programs, which have inspired chemists and physicians for millennia. 1,2 However, specic action mechanisms and target locations appear to be the bottleneck for further development of natural products. Therefore, novel strategies or combined methodologies are required to decipher complex systems.…”
Section: Introductionmentioning
confidence: 99%